Unusual Presentation of Epidural Haematoma with Ossified Border on Computed Tomography Scan - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Ossified epidural haematoma is a rare finding in clinical practice. Neuroimaging such as computed tomographic (CT) scan plays an important role in its diagnosis and management. A 58-year-old man came for brain CT on account of 4-month history of epilepsy. He had a history of road traffic accident 4 years ago. A radiologic diagnosis of ossified epidural haematoma was made as the working diagnosis.